2017
DOI: 10.5194/isprs-archives-xlii-4-w5-107-2017
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Built-Up and Green Areas on the Land Surface Temperature of the Kuala Lumpur City

Abstract: ABSTRACT:A common consequence of rapid and uncontrollable urbanization is Urban Heat Island (UHI). It occurs due to the negligence on climate behaviour which degrades the quality of urban climate condition. Recently, addressing urban climate in urban planning through mapping has received worldwide attention. Therefore, the need to identify the significant factors is a must. This study aims to analyse the relationships between Land Surface Temperature (LST) and two urban parameters namely built-up and green are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
3
1
0
1
Order By: Relevance
“…While a Mature green cover needs to be planted and maintained within an area to balance the negative effect of the built-up area. This result is in line with (Isa 2017) point out that the two urban parameters NDVI and NDBI have significant effects on the LST; and confirmed that built-up areas have a greater influence on the LST as compared to the green areas.…”
Section: Results Of Lst Ndvi and Ndbisupporting
confidence: 90%
“…While a Mature green cover needs to be planted and maintained within an area to balance the negative effect of the built-up area. This result is in line with (Isa 2017) point out that the two urban parameters NDVI and NDBI have significant effects on the LST; and confirmed that built-up areas have a greater influence on the LST as compared to the green areas.…”
Section: Results Of Lst Ndvi and Ndbisupporting
confidence: 90%
“…A mature green cover needs to be planted and maintained within an area to balance the negative effect of the built-up area. This result is in line with that of Isa et al (2017), who noted that the two urban parameters NDVI and NDBI have significant effects on the LST and confirmed that built-up areas have a greater influence on the LST than green areas.…”
Section: The Effects Of Built-up and Green Spaces On The Lst Of Addis...supporting
confidence: 92%
“…area. This result is in line with that of Isa et al (2017), who noted that the two urban parameters NDVI and NDBI have significant effects on the LST and confirmed that built-up areas have a greater influence on the LST than green areas.…”
Section: Estimation Of Lst For Sub-cities In Addis Ababasupporting
confidence: 92%
“…Por sua vez, o número de variáveis consideradas variou entre os diferentes trabalhos. Observou-se que, de um modo geral, ocorreu a avaliação entre duas variáveis dependentes (Li et al, 2017;Isa;Wan Mohd;Salleh, 2017;Agathangelidis;Cartalis;Santamouris, 2020;NGUYEN, 2020) e 36 (Alonso;Renard, 2020). A Figura 10 apresenta a distribuição do número de variáveis na amostra aderente.…”
Section: Figura 9 -Distribuição Dos Modelos De Regressão Utilizados N...unclassified